Comparison of maternal and child health service performances following a leadership, management, and governance intervention in Ethiopia: a propensity score matched analysis - Mesele Damte Argaw; Binyam Fekadu Desta; Sualiha Abdlkader Muktar; Wondwosen Shiferaw Abera; Ismael Ali Beshir; Israel Ataro Otoro; Asegid Samuel; Deirdre Rogers; Kristin Eifler (BMC Health Services Research, 2021)
Abstract Background Leadership, management, and governance (LMG) interventions play a significant role in improving management systems, enhancing the work climate, and creating responsive health systems. Hence, the Ethiopian Ministry of Health with the support of the USAID Transform: Primary Health Care project has been implementing LMG interventions to improve performances of primary healthcare entities. The purpose of this evaluation was to compare maternal and child health service performances and overall health system strengthening measurement results of primary health care entities by LMG intervention exposed groups. Methods The study used a cross-sectional study design with a propensity matched score analysis, and was conducted from August 28, 2017, to September 30, 2018, in Amhara, Oromia, Tigray, and Southern Nations, Nationalities, and Peoples’ (SNNP) regions. Data collection took place through interviewer and self-administered questionnaires among 227 LMG intervention exposed and 227 non-exposed health workers. Propensity score matched analysis was used to balance comparison groups with respect to measured covariates. Results The mean overall maternal and child health key performance indicator score with standard deviation (± SD) for the LMG intervention exposed group was 63.86 ± 13.16 and 57.02 ± 13.71 for the non-exposed group. The overall health system strengthening score for the LMG intervention exposed group (mean rank = 269.31) and non-exposed group (mean rank = 158.69) had statistically significant differences (U = 10.145, z = − 11.175, p = 0.001). In comparison with its counterpart, the LMG exposed group had higher average performances in 3.54, 3.51, 2.64, 3.00, 1.07, and 3.34 percentage-points for contraceptive acceptance rate, antenatal care, skilled birth attendance, postnatal care, full immunization, and growth monitoring services, respectively. Conclusion There were evidences on the positive effects of the LMG intervention on increased maternal and child health services performances at primary healthcare entities. Moreover, health facilities with LMG intervention exposed health workers had higher and statistically significant differences in management systems, work climates, and readiness to face new challenges. Therefore, this study generated evidence for integrating LMG interventions to improve the performance of primary healthcare entities and maternal and child service uptake of community members, which contributes to the reduction of maternal and child deaths.